Aberrant mTOR activation in senescence and aging: A mitochondrial stress response? - Nacarelli, Timothy (Exp Gerontol, 2014)
Unexpected activation of mTOR signaling, measured by ribosomal S6 phosphorylation or ribosomal S6 kinase (p70S6K) activity, has been reported in aging-related settings. Evidence of elevated mTOR activity has been reported in heart and muscle tissue in aged mice and humans, mouse models of progeria, and senescent human fibroblasts. We explore these reports and the possibility that activation of the mTOR/p70S6K kinase pathway may represent a ROS-mediated response to mitochondrial stress leading to the activation of senescence. This activation is a hallmark of both aged tissue and senescent human cells.